Environmental and sustainability education in the Caribbean: Crucial issues, critical imperatives. Issue 6 (2nd June 2020) - Ferguson, Therese
Abstract: The development, quality and impact of environmental and sustainability education (ESE) in the Caribbean have received increased attention from a growing body of education researchers over the past few decades. This is not surprising given that the region has been grappling with various environmental, social, and economic sustainability issues, and education remains widely regarded as a key mode of response by a range of stakeholders, networks and commentators. Drawing on local to wider perspectives and initiatives, formal and non-formal ESE activities have been undertaken, to enhance knowledge and awareness, develop values, hone skills, and promote behaviours consistent with sustainable development. Whilst this increased engagement is significant and heartening, I argue that there is still scope for a renewal of focus in ESE in the Caribbean, honing in on four main areas: climate change education, the environment and violence nexus, teacher education, and universities as models of and for sustainability. These areas are consistent with regional sustainability imperatives and the global Sustainable Development Goals (SDGs), as well as ripe for deeper research-practice interlinkages. An overview of existing fields of educational inquiry in the Caribbean is offered, along with the four foci for further and future research, with the hope that new, emerging and established academics (as well as practitioners) work productively together to engage these crucial issues and critical imperatives for ESE. Abstract :